Pregunta
(b) \( \frac{3}{p}+\frac{5}{2 p}-\frac{2}{p^{2}} \)
Ask by Coles Mullins. in Australia
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
The simplified expression is \( \frac{11p - 4}{2p^{2}} \).
Solución
To simplify the expression:
\[
\frac{3}{p} + \frac{5}{2p} - \frac{2}{p^{2}}
\]
**Step 1: Combine Like Terms**
First, combine the terms that have the same denominator:
\[
\frac{3}{p} + \frac{5}{2p} = \frac{6}{2p} + \frac{5}{2p} = \frac{11}{2p}
\]
**Step 2: Combine All Terms Over a Common Denominator**
Now, combine the result with the remaining term:
\[
\frac{11}{2p} - \frac{2}{p^{2}}
\]
To combine these, find a common denominator, which is \(2p^{2}\):
\[
\frac{11}{2p} = \frac{11p}{2p^{2}}
\]
\[
\frac{2}{p^{2}} = \frac{4}{2p^{2}} \quad (\text{since } \frac{2}{p^{2}} = \frac{4}{2p^{2}})
\]
Now, subtract the fractions:
\[
\frac{11p}{2p^{2}} - \frac{4}{2p^{2}} = \frac{11p - 4}{2p^{2}}
\]
**Final Simplified Expression:**
\[
\frac{11p - 4}{2p^{2}}
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
To simplify the expression \( \frac{3}{p}+\frac{5}{2 p}-\frac{2}{p^{2}} \), we first find a common denominator. The common denominator for all terms is \( 2p^2 \). Rewriting each term: - \( \frac{3}{p} = \frac{3 \cdot 2p}{2p^2} = \frac{6p}{2p^2} \) - \( \frac{5}{2p} = \frac{5 \cdot p}{2p^2} = \frac{5p}{2p^2} \) - \( \frac{2}{p^2} = \frac{2 \cdot 2}{2p^2} = \frac{4}{2p^2} \) Now, combine them: \[ \frac{6p + 5p - 4}{2p^2} = \frac{11p - 4}{2p^2} \] So, the simplified expression is \( \frac{11p - 4}{2p^2} \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium